PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING - Libyanita, Mayangtari; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the influence of intellectual capital to the financial performance of Syariah banking with competitive advantage as the intervening variable. The population is Syariah Commercial Banks which are listed in Bank Indonesia in 2010-2014 periods which is done by using the financial statement data which has been obtained by using purposive sampling and based on the determined criteria, so ten Syariah Commercial Bank which have met the criteria have been selected as samples. The criterion of sample collection are: 1) Syariah Commercial Banks which are listed inBnak Indonesia; 2) Syariah Commercial Banks which consecutively publish their annual financial statement in 2010-2014; 3) Syariah Commercial Bankswhich have a complete data that is required in the research variable and the syariah commercial banks have positive profit. The analysis technique has been done by using linear regressions analysis and path analysis. Based on the result of linear regressions analysis and path analysis with its significance rate is 5% so that the result of this research shows that: 1) VAIC variable has significant and positive influence to the CA. 2) CA variable has significant and positive influence to the ROA. 3) VAIC variable has significant and positive influence to the ROA. 4) CA variable is mediated VAIC to the ROA.Keywords: Intellectual Capital, Competitive Advantage, Return On Assets